2003
DOI: 10.1128/iai.71.11.6141-6147.2003
|View full text |Cite
|
Sign up to set email alerts
|

One of Two Human Lactoferrin Variants Exhibits Increased Antibacterial and Transcriptional Activation Activities and Is Associated with Localized Juvenile Periodontitis

Abstract: The iron-binding protein lactoferrin is a ubiquitous and abundant constituent of human exocrine secretions. Lactoferrin inhibits bacterial growth by sequestering essential iron and also exhibits non-iron-dependent antibacterial, antifungal, antiviral, antitumor, anti-inflammatory, and immunoregulatory activities. All of these non-iron-dependent activities are mediated by the highly charged N terminus of lactoferrin. In this study we characterized a Lys/Arg polymorphism at position 29 in the N-terminal region o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
94
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 48 publications
(49 reference statements)
6
94
0
4
Order By: Relevance
“…Human neutrophil-specific granule deficiency, caused by a mutation in the C/EBP trancription factor (39), also results in decreased or absent neutrophil LF (among many other specific granule proteins) (40,41), and is associated with an increased risk of pyogenic bacterial infections, but not fungal infection. Several single nucleotide polymorphisms in human LF have been reported and are associated with an increased risk for periodontitis possibly by altering the oral microflora (42,43); however, it is unknown whether these polymorphisms are risk factors for aspergillosis. Despite the overall similarity between normal and CGD PMN and their postsecretory supernatants in arresting the growth of A. fumigatus conidia, we found that CGD PMN actually contained less LF than normal PMN.…”
Section: Discussionmentioning
confidence: 99%
“…Human neutrophil-specific granule deficiency, caused by a mutation in the C/EBP trancription factor (39), also results in decreased or absent neutrophil LF (among many other specific granule proteins) (40,41), and is associated with an increased risk of pyogenic bacterial infections, but not fungal infection. Several single nucleotide polymorphisms in human LF have been reported and are associated with an increased risk for periodontitis possibly by altering the oral microflora (42,43); however, it is unknown whether these polymorphisms are risk factors for aspergillosis. Despite the overall similarity between normal and CGD PMN and their postsecretory supernatants in arresting the growth of A. fumigatus conidia, we found that CGD PMN actually contained less LF than normal PMN.…”
Section: Discussionmentioning
confidence: 99%
“…However, from studying different ethnic populations, the data could not help explain why African Americans appear to be more susceptible to periodontitis due to this organism. 22 In the present report, we examine further the genetic associations between this gene and aggressive periodontal disease in both African-American and Caucasian populations, using a novel, nonconservative, SNP in the human lactoferrin gene. …”
mentioning
confidence: 99%
“…One recent study has identified two variants of lactoferrin and demonstrated that these variants exhibit different antibacterial and transcriptional activation activities. 22 Examination of a small population of periodontal patients suggested that these differences may go some way in explaining susceptibility to periodontal disease. However, from studying different ethnic populations, the data could not help explain why African Americans appear to be more susceptible to periodontitis due to this organism.…”
mentioning
confidence: 99%
“…Velliyagounder et al (13) found that a Lys/Arg polymorphism (rs1126478) at position 29 in the N-terminal region of human LTF produced functional differences, and Expression levels of JNK associated with polymorphic lactotransferrin haplotypes in human nasopharyngeal carcinoma that this difference may contribute to the pathogenesis of localized juvenile periodontitis. Similarly, control individuals who were G carriers at rs1126478 had significantly lower fasting triglyceride concentrations and significantly higher high-density lipoprotein cholesterol concentrations than AA homozygotes (14).…”
Section: Introductionmentioning
confidence: 99%